Comparative study of KI-67 and CD44 expression in serrated polyps of the distal colon - M. A. Shyshkin; T. O. Khrystenko (Kazimierz Wielki University, 2020)
Introduction. Serrated polyps are newly distinguished types of colonic polyps. Nowadays lots of questions about serrated neoplastic pathway are still unclear. The purpose of the study was to compare Ki-67 and CD44 immunohistochemical (IHC) expression levels in different histological types of serrated polyps. Materials and methods. Histopathological and IHC studies of 30 serrated polyps were conducted. IHC study was carried out using antibodies against Ki-67 and CD44. Results of IHC reactions with antibodies against Ki-67 were estimated by immunostained nuclei counting and were expressed in proliferation index (PI) while results of IHC reactions with antibodies against CD44 were estimated by photo digital morphometry and were expressed in immunostained cells relative area (%). Furthermore, distribution of Ki-67+ and CD44+ cells in colonic crypts was examined. Results. It was revealed that hyperplastic polyps (HP) were characterized by medium PI and basal-middle pattern of Ki-67+ cells distribution. HP were also characterized by the median of CD44+ cells area equal to 22,36 (13,15;30,41) % and basal-middle pattern of CD44+ cells distribution. Herewith, direct medium strength correlation between Ki-67 and CD44 expression levels in HP was established. Traditional serrated adenomas (TSA) were characterized by medium PI and diffuse pattern of Ki-67+ cells distribution. TSA were also characterized by the median of CD44+ cells area equal to 25,48 (15,19;29,04) % and upper-middle pattern of CD44+ cells distribution. Direct weak strength correlation between Ki-67 and CD44 expression levels in TSA was established. Sessile serrated adenomas (SSA) were characterized by medium PI and basal pattern of Ki-67+ cells distribution. SSA were also characterized by the median of CD44+ cells area equal to 20,54 (11,25;28,15) % and basal-middle pattern of CD44+ cells distribution. Direct medium strength correlation between Ki-67 and CD44 expression levels in SSA was established.